Diatom assemblage of the sediment short core EN18232-1, Lake Khamra, Siberia - Amelie Stieg; Boris K Biskaborn; Ulrike Herzschuh; Luidmila A Pestryakova; Hanno Meyer (PANGAEA, 2025)
This data set is an extension to the previously published data in a bundled publication (Stieg et al., 2024a) from the Russian Lake Khamra (59.99°N, 112.98°E, 340 m a.s.l.), located in eastern Siberia in SW Yakutia. The short core (EN18232-1) was retrieved in summer 2018 and subsampled in 2021 in 39 continuous 1 cm increments covering the last 220 years (ca. 2015-1790 CE). Detailed information about the age-depth model of the short core EN18232-1 can be found in the research paper (Stieg et al., 2024b). We provide diatom assemblage data for the 39 samples of the short core EN18232-1. We used aliquots of 0.10 g freeze-dried sample material. The slide preparation followed the common procedure (Battarbee et al., 2001). 5 ml of Microsphere suspension (2 x 10^6 microspheres ml-1) were added to estimate the diatom valve concentration (DVC, valves g-1). We used a ZEISS AXIO Scope.A1 light microscope with a Plan-Apochromat 100x/ 1.4 Oil Ph3 objective at 1000x magnification to identify diatom species to lowest possible taxonomic level. We counted a minimum of 350 diatom valves in each sample (mean: 391 valves). To assess the diatom valve dissolution, we determined the F index by dividing the diatom counts into dissolved and pristine categories. The F index has a total range between 0 and 1, whereby 1 equals a perfect preservation. We calculated the diatom accumulation rates (DARs, 10^9 valves m-2 a-1) by multiplying DVC with mass accumulation rates (MAR, g cm-2 a-1), available in a previous published data set (Stieg et al., 2024c), and multiplying it by 100. Additionally, we estimated scales of Mallomonas and Crysophyt cysts without further specification. More details according to the methods can be found in Stieg et al. (in process).